Developing Customer Engagement Through Instagram Social Media on Local Coffee Shop - Retno Lies Setyawati; Rina Anindita (Majalah Ilmiah Bijak, 2022)
Since COVID-19 has been declared as pandemic, many business sectors are affected, including food and beverage sector. As social distancing plays role in the current health protocol to prevent the mutation of Coronavirus, it is highly recommended for customers to buy food or drink in online mode rather than visiting the restaurants or coffee shops. Nevertheless, this online mode buying process would loose the emotional bond between the brand and the customers. Therefore, the marketing strategy through social media is believed as a way to maintain the emotional bond. The purpose of this research is to find out the precise model to increase the Kopi Kekinian’s customers’ participation on Instagram to strengthen the bond. The methods applied in this research is survey by distributing questionnaire for survey and by applying one-shot study data collection. The result was obtained from 155 respondents, during the data collection process from April to June 2021. The method to test the model is by applying Chi Square, ANOVA Test, and Logistic Regression. Moreover, the research result shows that the customer engagement affects the customer participation on local coffee shop brand’s Instagram social media, whereas the posting time, which plays role as the moderation that consists of weekdays and weekend, does not determine the connection between the customer engagement and the customer participation on the local coffee shop brand’s Instagram social media.